Criterion of Client’s Company, Public Accountant Firm, Financial Distress, and Company Growth Towards Auditor Switching - Annisa Adha; Muchammad Noch (TRIKONOMIKA, 2017)
There were some factors why company switched its auditor voluntarily, that were criterion of client’s company, criterion of public accountant firm, financial distress, and company growth. Population in this study was a manufacture company’s financial report in the sector of Basic and Chemical Industry, by the amount of 65 companies listed in Indonesia Stock Exchange in the period of 20102015. A method used was purposive sampling that is 13 companies. The analytical tool used is logistic regression analysis. The results showed that the criterion of client’s company and company growth statistically did not give any influence towards auditor switching. Meanwhile, the criterion of public accountant firm and financial distress did give influence towards auditor switching.